Peningkatan Pencapaian KPI Timeliness Pada Human Resource Department PT. X - Ruth Yolanda Patricia Cahyono; Debora Anne Yang Aysia (Jurnal Titra, 2015)
PT. X is an international manufacturing company. In October 2015, the work system at Human Resource Department (HRD) PT X has been changed. There are two new Key Performance Indicators (KPIs) as the impact of the changes. One of the new indicators is timeliness, which must be achieved by the specialist team at HRD. The target of timeliness indicator is 97% while the average achievement is still about 62.6%. This research aims is increasing the achievement of timeliness indicator. There are two suggestions that have been made. They are providing a reminder tool for specialist team and changing specialist team’s work system. Reminder tool is useful as a job reminder for specialist team. Specialist work system is changed by dividing the role of each specialist based on the type of existing processes, so specialist will be more focus with their task. The reminder tool has been implemented for three months, and as a result the timeliness indicator achievement is increase to 93%.